Epixylic microbial communities as key regulators of methane emissions from submerged wood in a tropical hydroelectric reservoir - Fanny Colas; Léa Cabrol; Jean‐Marc Baudoin; Yves Prairie; Jacques Beauchêne; Vincent Chanudet; Etienne Dambrine; Sophie Guasco; Frederick Jacob; Arthur Szylit; Corinne Valette; Régis Vigouroux; et al. (Limnology and Oceanography, 2026)
Tropical hydroelectric reservoirs are recognized hotspots for greenhouse gas emissions, yet the role of submerged forests in these emissions remains poorly understood. In this study, we investigated the contribution of standing dead trees and their associated epixylic biofilms to methane (CH 4 ) and carbon dioxide (CO 2 ) emissions in the permanently stratified Petit Saut reservoir, French Guiana. We conducted in situ measurements of greenhouse gas fluxes from submerged trunks at multiple depths using static chambers. To unravel the microbial mechanisms underlying CH 4 dynamics, we characterized the active microbial communities and quantified methane production and oxidation rates in both wood and biofilm samples collected above and below the oxycline, using 16S rRNA sequencing and laboratory incubations. Our findings revealed that submerged wood serves as an unrecognized source of in situ CH 4 production, primarily via acetoclastic methanogenesis dominated by Methanosaeta . In contrast, epixylic biofilms acted as effective CH 4 sinks, with methane oxidation largely driven by Methylocystis . Microbial composition and activity showed strong vertical stratification, closely linked to oxygen availability. In situ fluxes mirrored these microbial patterns, with net CH 4 and CO 2 efflux observed below the oxycline and net influx above it. This study highlights the dual role of submerged wood and its surface biofilms in CH 4 cycling, emphasizing the importance of microbial interactions in regulating greenhouse gas emissions from flooded tropical forests. These findings underscore the need to include wood‐mediated processes in greenhouse gas budgets of tropical reservoirs, especially as dam construction continues to expand in forested tropical regions.

Greenhouse gas dynamics in fishponds: management versus environmental controls in a complex aqua-agriculture system, France - Emma Mari; Fanny Colas; Sylvain Dolédec; Anas M. Usoof; Jules Blanc; Björn Wissel (Journal of Environmental Management, 2025)

Relative Effects of Eutrophication and Warming on Freshwater Ecosystems Across Ecological Levels - Valentin Marin; Fanny Colas; Stéphanie Boulêtreau; Julien Cucherousset (Global Change Biology, 2025)
Global change strongly alters biodiversity worldwide, but our ability to predict their consequences for ecosystem functioning remains limited. This lack of knowledge may be attributed to the limited empirical evidence of the simultaneous ecological impacts of global change across multiple ecological levels. Here, we conducted a full factorial experiment to measure the isolated and combined effects of two global change drivers to which freshwater ecosystems are severely exposed: (i) nutrient addition, which mainly affects the lower trophic levels and modifies ecosystems from the bottom of the food chain, and (ii) warming, which primarily affects large organisms at the top of the food chain. We quantified the effects of the two global change drivers at four different ecological levels: community composition (zooplankton and benthic invertebrates), size structure, trophic architecture, and ecosystem functioning. We found that the impacts of treatments varied significantly across different ecological levels. Specifically, community composition was predominantly affected by warming, whereas nutrient addition played a more important role than warming in ecosystem functioning (e.g., primary production and atmospheric CO 2 uptake). More importantly, we found that food webs (described using size spectrum and stable isotope structure) represent an integrative ecological level for capturing the effects of the two global change drivers tested, integrating changes in both community structure and ecosystem functioning. These results provide valuable insights into the responses of aquatic ecosystems to global change and reveal the importance of considering multiple ecological levels to improve our understanding of the processes driving the responses of ecosystems to global change.

Sulfides as environmental stressors in Paracas Bay, Peru - Fanny Rioual; Jonathan Flye-Sainte-Marie; David Point; François Colas; Tomasa Cuellar-Martinez; Jorge Tam; Kevin Diaz; Wilson Carhuapoma; Michelle Graco; Fred Jean; Arturo Aguirre-Velarde (Marine Pollution Bulletin, 2025)

Floating photovoltaics strongly reduce water temperature: A whole-lake experiment - Regina L.G. Nobre; Chloé Vagnon; Stéphanie Boulêtreau; Fanny Colas; Frédéric Azémar; Loïc Tudesque; Nathalie Parthuisot; Paul Millet; Julien Cucherousset (Journal of Environmental Management, 2025)

Warming drives feedback between plant phenotypes and ecosystem functioning in sub-Antarctic ponds - Pauline Douce; Laurent Simon; Fanny Colas; Florian Mermillod-Blondin; David Renault; Cécile Sulmon; Pauline Eymar-Dauphin; Roman Dubreucque; Anne-Kristel Bittebiere (Science of The Total Environment, 2024)

Influence of combined temperature and food availability on Peruvian anchovy (Engraulis ringens) early life stages in the northern Humboldt Current system: A modelling approach - Jorge Flores-Valiente; Christophe Lett; François Colas; Laure Pecquerie; Arturo Aguirre-Velarde; Fanny Rioual; Jorge Tam; Arnaud Bertrand; Patricia Ayón; Saidou Sall; Nicolas Barrier; Timothée Brochier (Progress in Oceanography, 2023)

Benthic indicators of sediment quality associated with run-of-river reservoirs - Colas Fanny; Archaimbault Virginie; Férard Jean-François; Bouquerel Jonathan; Roger Marie-Claude; Devin Simon (Hydrobiologia, 2013)